Alternating Alpha-Series Process - Arnold, R; Chukova, S; Hayakawa, Y; Marshall, S (Nanjing Tech University, China, Nanjing University of Aeronautics and Astronautics, China, 2021)
The alternating α-series process (AAS process) can be used to study ageing repairable systems whose lifetime can be modelled as an alternating sequence of operational times and repair times. In this paper the AAS process is defined, and two key counting processes associated with the AAS process are analysed. The AAS process and results in this paper can be applied in fields such as warranty, maintenance and reliability cost analysis.